AN ANALYSIS ON THE ENGLISH TEACHERS STRATEGIES IN TEACHING READING COMPREHENSION SMP 1 WONOMULYO - Sarjan, Nurmadia; Mardiana, Hj. (ETERNAL (English, Teaching, Learning, and Research Journal), 2017)
The research problems of this research, what were the strategies of English teacher in teaching reading comprehension at the Second Grade of Junior High School 1 of Wonomulyo and how the implement of English teacher’ strategies in teaching reading comprehension at the Second Grade of Junior High School 1 of Wonomulyo? The method of this research was qualitative reseacrh. The subject of this research was English teacher in Junior High School 1 of Wonomulyo. The instrument of this research were observation ceklist and interview. The result of the research found that two strategies that the teacher used, Scaffolding and QARs ( Question Answer Relationship). Scaffolding strategy student can develop about idea which readable by the student. QARs ( Question Answer Relationship), the teacher able to know how far their students understand what the teacher has given to them. And the teacher able to know how far understanding of the student doing the task after read the text that has been given and the students guided to more focus on the text and understand what the content of the text.